2020
DOI: 10.1097/md.0000000000019780
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up results in patients with thoracolumbar unstable burst fracture treated with temporary posterior instrumentation without fusion and implant removal surgery

Abstract: Segmental fusion is not necessarily needed in treatment of thoracolumbar unstable burst fracture requiring surgery. Our objective was to report the results of follow-up for at least 10 years in patients with thoracolumbar unstable burst fracture requiring surgery in which fractured segment was healed following temporary posterior instrumentation without fusion, and in whom implants were subsequently removed. Retrospective Cohort Study. Nineteen patients in whom union of fractured verteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 33 publications
0
31
0
Order By: Relevance
“…Two studies by Ko et al both state that there is no significant difference in average anterior body height ratio (ABHR) after removal surgery and correction is maintained. 29,36 This is supported by the stable AVH that Chen et al observed with minimal loss from surgery (97.6% + 6.5%) to final follow-up 94.3% + 5.9%. 28 However, Kim et al found evidence of vertebral height loss of 15.3% after implant removal rising to 17.4% at final follow-up (p < 0.01).…”
Section: Vertebral Body Angle and Vertebral Body Ratiomentioning
confidence: 63%
See 2 more Smart Citations
“…Two studies by Ko et al both state that there is no significant difference in average anterior body height ratio (ABHR) after removal surgery and correction is maintained. 29,36 This is supported by the stable AVH that Chen et al observed with minimal loss from surgery (97.6% + 6.5%) to final follow-up 94.3% + 5.9%. 28 However, Kim et al found evidence of vertebral height loss of 15.3% after implant removal rising to 17.4% at final follow-up (p < 0.01).…”
Section: Vertebral Body Angle and Vertebral Body Ratiomentioning
confidence: 63%
“…34,38,40 In a similar manner, Ko et al reported statistically significant improvement in Oswestry Disability Index (ODI) scores from 15.86 + 7.93 to 7.96 + 7.38 at last follow-up (p < 0.001). 29 Jeon et al concurred with this finding when they noted that mean ODI at implant removal was 26.6 + 10.4 improving to 16.3 + 11.5 at 1-year follow-up (p ¼ 0.000), which was further reduced to 12.7 + 8.1 (p ¼ 0.000) at 2 years. In patients with neurological deficit who registered exceptionally high disability indices, Chen et al witnessed a remarkable fall in disability from 86.1 + 8.8 preoperatively to 15.9 + 6.4 (p < 0.05) at 1 year, and a further improvement to 8.4 + 4.6 at final follow-up.…”
Section: Quality Of Lifementioning
confidence: 77%
See 1 more Smart Citation
“…However, it was reported that this procedure was an effective treatment in patients with thoracolumbar unstable burst fracture who had a McCormack load-sharing score of less than 7 points. 27 Percutaneous fixation alone 28 without grafting or with thoracoscopically assisted corpectomy 29 is sufficient for treating thoracolumbar burst fractures with satisfactory results. Minimally invasive techniques provide more advantages than traditional open approaches in the treatment of thoracolumbar burst fractures.…”
Section: Discussionmentioning
confidence: 99%
“…As these ligamentous injuries may not heal effectively, the safety of hardware removal after bony healing may be questioned. However, there is increasing evidence that thoracolumbar injuries with a ruptured PLC may be effectively treated by temporary spinal fixation without fusion, with little to no progressive kyphosis or sagittal imbalance being reported up to 10 years after hardware removal (Figures 8a, 8b) [38,46,53,66,74]. showing no increased kyphosis.…”
Section: Spinal Instrumentation Removalmentioning
confidence: 99%